2003
DOI: 10.1103/physrevlett.90.026801
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties ofC60Polymers

Abstract: Magnetic properties of various C60 polymers are calculated using tight-binding molecular-dynamics and ab initio methods. Our results suggest a mechanism involving an interplay between structural defects and sp(3) hybridization to be responsible for the origin of this magnetism. The onset of magnetism is found to occur much more readily for the Rh-C60 polymeric phase with defects than for any of the other polymers, in agreement with the recent experiment. Our estimate of the magnetic moment is also in very good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 21 publications
7
95
1
Order By: Relevance
“…In addition to polymerized fullerenes, 120 nanotubes, 121 graphite, 122 and nanodiamonds, 123 magnetism was recently reported for graphene produced from graphene oxide. 124 On the basis of calculations, the observed magnetic behavior in all these systems was explained in terms of defects in the graphitic network (either native or produced by ion irradiation) such as under-coordinated carbon atoms, for example, vacancies, 125 interstitials, 126 carbon adatoms, 47 and atoms at the edges of graphitic nanofragments with dangling bonds either passivated with hydrogen atoms or free. 127 Such defects have local magnetic moments and may give rise to flat bands and eventually to the development of magnetic ordering.…”
Section: Properties Of Defective Graphenementioning
confidence: 99%
“…In addition to polymerized fullerenes, 120 nanotubes, 121 graphite, 122 and nanodiamonds, 123 magnetism was recently reported for graphene produced from graphene oxide. 124 On the basis of calculations, the observed magnetic behavior in all these systems was explained in terms of defects in the graphitic network (either native or produced by ion irradiation) such as under-coordinated carbon atoms, for example, vacancies, 125 interstitials, 126 carbon adatoms, 47 and atoms at the edges of graphitic nanofragments with dangling bonds either passivated with hydrogen atoms or free. 127 Such defects have local magnetic moments and may give rise to flat bands and eventually to the development of magnetic ordering.…”
Section: Properties Of Defective Graphenementioning
confidence: 99%
“…These, in turn, can be coupled ferromagnetically with the mediating services of another type of codopant (defect) 1,[23][24][25][26] . One can, thus, invoke the existence of a dormant bipartite structure with the potential to get activated in the presence of the appropriate codopants.…”
Section: B Defect Synergymentioning
confidence: 99%
“…This led to the suggestion 1,[23][24][25][26] that the enhanced magnetism found in bipartite codopant structures we studied [(Ti(3Co,2Cr)O 2 , Ga(Co,Cu)N, Zn(Co,Cu)O and Ga(Mn,Cu)N) as well as C-based materials], is reminiscent of proposed bipartite model descriptions spanning a diverse sample of electronic processes considered to have a leading role in developing magnetic features. The models referred to in this context included the following:…”
mentioning
confidence: 99%
“…Earlier simulations showed that CA and some other defects in nanotubes and other carbon nanomaterials 95,96 can have local magnetic moments. Although the standard STM with the tip made from a nonmagnetic material probes simultaneously the LDOS corresponding to majority and minority spins, an account for magnetism can change the positions of defect-induced peaks.…”
Section: G Spin-polarized Calculationsmentioning
confidence: 99%